Postcolonial life narratives: testimonial transactions - Whitlock, Gillian (Oxford studies in postcolonial literatures, 2015)
The 'Oxford Studies in Postcolonial Literatures' series offers stimulating and accessible introductions to definitive topics and key genres and regions within the rapidly diversifying field of postcolonial literary studies in English. 'Postcolonial life narrative' draws together two dynamic fields of contemporary literature and criticism, postcolonialism and life narrative, to create a new assemblage: postcolonial life narrative. Focusing in particular on testimonial narrative, from slave narrative in the late eighteenth century to contemporary Anglophone life narrative from Africa, Australia, the Caribbean, Palestine, North America, and India, this study follows texts on the move through adaptation, appropriation, and remediation. For postcolonial subjects life narrative offers extraordinary opportunities to present accounts of social injustice and oppression, of violence and social suffering. Testimonial narrative can reach across cultures to produce intimate attachments between those who testify and those who bear witness to legacies of apartheid, slavery, rape warfare, genocide, and dispossession. Thresholds of testimony are subject to change and for some, for example refugees and asylum seekers, opportunities to engage a witnessing public and inspire campaigns for social justice on their behalf are curtailed-these are the 'ends of testimony'. The production, circulation, and reception of testimonial life narrative connects directly to the most fundamental questions of who counts as human, what rights follow from this, and what makes for grievable life. Postcolonial life narrative is a dynamic field of literature and criticism, and this book presents a series of proximate readings that outline its distinctive imaginative geographies.